Morphological variation of reproductive structures of the Solanaceae in the Yanachaga-Chemillén National Park (Peru) - Gonzáles, Paúl; Laboratorio de Florística, Departamento de Dicotiledóneas, Museo de Historia Natural. Universidad Nacional Mayor de San Marcos. Av. Arenales 1256, Jesús María (2020)
Morphological variation of reproductive structures of the Solanaceae in the Yanachaga- Chemillén National Park (Peru). This study analyzes the presence and variation of floral features in species of the Solanaceae family in three localities of the Yanachaga-Chemillén National Park (Perú) during the rainy season from Feb–Mar of 2009. The morphometric data collection of the flowers and fruits of 280 individuals, belonging to 47 species, collected in the towns of Paujil (400 m), Tunqui (1900 m) and San Daniel (2400 m) was analyzed. The quantitative data was analyzed using Spearman’s simple correlation, while for the qualitative data, a descriptive statistical analysis was performed. The analysis of the quantitative data indicates that there are statistically significant variation in the size of certain flower structures, which have a moderate negative correlation with their altitudinal distribution, these variables are the length of the corolla tube (p = 0.000358) and the style (p = 0.00060). Within the qualitative data it was observed that the color of the flowers presents a variation according to the altitude, where the white color has a greater predominance in the Tunqui and San Daniel localities located at 1900 m and 2400 m respectively, while the yellow flowers are more common in Paujil at 450 m. Additionally, it was found that the greatest diversity of species and the greatest variability of the reproductive characters analyzed were registered at 2400 m of altitude. Variations and predominance of reproductive characteristics could be related to the different types of pollinators for species in this family.